Practical and Highly Stereoselective Synthesis of Trisubstituted (E)-α,β-Unsaturated Esters - Ozeki, Minoru; Egawa, Honoka; Kuse, Akiko; Takano, Toshiki; Yasuda, Narumi; Mizutani, Hideki; Izumiya, Sumire; Nakashima, Daichi; Arimitsu, Kenji; Miura, Takuya; Kajimoto, Tetsuya; Hosoi, Shinzo; Iwasaki, Hiroki; Kojima, Naoto; Node, Manabu; Yamashita, Masayuki (Synthesis, 2015)
Trisubstituted (E)-α,β-unsaturated esters bearing various substituents were synthesized with high geometrical selectivity by using three reactions: an aldol reaction, acetylation of the hydroxy group at the β-position, and an E1cB reaction induced by 1,8-diazabicyclo[5.4.0]undec-7-ene. The method does not require separation of the diastereoisomeric mixture of β-hydroxy ester intermediates before the E1cB reaction, and is usable for gram-scale syntheses of trisubstituted (E)-α,β-unsaturated esters.
Keywords: stereoselective synthesis; enoates; aldol reactions; acylations; elimination reactions